From the past, a long way to future challenges for a greater control of tuberculosis - Villa, Simone; Riccardi, Niccolò; Canetti, Diana; Alagna, Riccardo; Castellotti, Paola; Ferrarese, Maurizio; Cirillo, Daniela; Barberis, Ilaria; Bragazzi, Nicola Luigi; Gazzaniga, Valentina; Ricucci, Valentina; Codecasa, Luigi Ruffo; et al. (Tuberculosis (Edinburgh, Scotland), 2020)
Tuberculosis (TB) and humans have coexisted for more than 40,000 years; however TB remains a global threat to human kind. The international community has developed new tools for early detection, but TB strains evolved acquiring resistance to first-line therapeutic drugs with increasing treatment challenges. Furthermore, TB has formed also an alliance with human immunodeficiency virus; in this way the poorest populations are most affected. The current vaccine planning activity includes 14 new vaccines against TB (11 of those in the phaseII/III) developed with different techniques. Now, more than ever, new anti-TB drugs and new anti-TB regimens are urgently required as well as universal health care and social protection in order to tackle down both hard to treat TB and the social determinants of TB. Coordinated actions and sharing of information are needed to aspire everywhere to the best clinical practices and improve quality of life of patients and their families.